SPECIES OF CONODERUS ESCH. WITH NOTES ON GENUS (CONODERINAE, ELATERIDAE : COLEOPTERA) - VATS, L.K.; CHAUHAN, R.L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
Eight new species of Conoderus Esch, viz. bicarinatius, nigripes, garhwalensis, tapovanensis, longipenis, chirakutensis, nigrolineatus and nigromaculosus have been described. All the species, except bicarinatus, were collected from the agricultural fields of North-West India. They are separated on the bases of shape of frontal margin, dimensions of pronotum and the number of carinae on its posterior angles, comparative length of antennal segment 2-4, colour of elytra and shape of its posterior extremities.